As consoantes sibilantes: oralidade, escrita e consciência fonológica - Esteves, Paula Margarida Lourenço (2013)
The main goal of this study is to analyse the influence of Speech and Sound Disorders, Phonological and Phonetic, associated with the production of sibilant consonants on the performance of reading and writing, as well as their relation with phonological awareness. In order to accomplish this goal, three groups were selected composed by children with Phonological Disorder, Phonetic Disorder and children without articulatory difficulties. Results suggest that children with Phonological Disorder tend to show difficulties in auditory discrimination and perception of sibilant consonants, transposing them to their reading and writing performance, through phonological errors. In contrast, children with Phonetic Disorder revealed average phonological and orthographic errors identical to those of the control group, except for tests involving pseudo-words. It was also possible to verify a correlation between phonological awareness and reading and writing performance, especially on the syllabic and phonemic levels.